ChemInform Abstract: Asymmetric Sharpless Dihydroxylation Reaction of Chiral Bishomoallylic Alcohols: Application to the Synthesis of the C1—C10—C5 Fragment of FR225654. Issue 18 (6th May 2014) - Mohammad, Shabbair; Dhambri, Sabrina; Gori, Didier; Vaxelaire, Carine; Sorin, Geoffroy; Ardisson, Janick; Lannou, Marie‐Isabelle
Abstract A series of different ligands is screened for the asymmetric dihydroxylation of bishomoallylic alcohols to produce 1, 2, 5‐pentanetriol derivatives.